Design of Web-Based Scheduling Applications Complain at PT. Nuansa Cerah Informasi Surabaya - Yudha, Rahardiyan Arya; Setyawan, Henry Bambang; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
: PT. Nuansa Cerah Informasi (NCI) is one of company that worked in software developer, maintenance software, IT project financing and Training & Consultant that which place in Bandung, it also has branch office in Surabaya. There was some of error during the software implementation in the module which caused by the stage process that is conducted inappropriate and also by some errors. During the process of complain there is always retardment because of improper handling of complaints, such as knowing from the rate of module rate’s importance error, the hospital status (costumer status), the hospital contract value, date of complain and category of complain that brings an impact to list complain queues. According to those problems, it will need some solution in schedule handling complain to PT. Nuansa Cerah Informasi, especially in Surabaya by designing a schedule application website base that can help to overcome the problems. Based on the results of trials that have been conducted with PT. NCI then this application can reduce delays in handling complaints for using the application can produce schedules rapidly complaint handling in accordance with company requirements.